2013
DOI: 10.1521/aeap.2013.25.2.112
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Examining Food Insecurity and HIV Risk Behaviors Among Individuals Recently Released From Prison

Abstract: Annually 700,000 individuals are released from U.S. prison, many at risk for food insecurity and HIV. The association between food insecurity and HIV risk behaviors has been established but not in this population. To investigate this association, we recruited 110 recently released prisoners to participate in a survey. Ninety-one percent of our sample was food insecure; 37% did not eat for an entire day in the past month. Those who did not eat for an entire day were more likely to report using alcohol, heroin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 41 publications
1
33
1
Order By: Relevance
“…(Wang et al 2013) Trained interviewers in San Antonio, TX, San Francisco, CA, and New Haven, CT, with a history of incarceration, recruited respondents from local reentry centers, halfway houses, homeless shelters, outdoor parks, or locations where individuals released from prison congregate, and administered a survey. Respondents were verbally consented and provided with $10 grocery vouchers for participation.…”
Section: Methodsmentioning
confidence: 99%
“…(Wang et al 2013) Trained interviewers in San Antonio, TX, San Francisco, CA, and New Haven, CT, with a history of incarceration, recruited respondents from local reentry centers, halfway houses, homeless shelters, outdoor parks, or locations where individuals released from prison congregate, and administered a survey. Respondents were verbally consented and provided with $10 grocery vouchers for participation.…”
Section: Methodsmentioning
confidence: 99%
“…Among low-income urban households in these countries, food insecurity may be associated with unstable and vulnerable housing situations, such as living in shelters, in 'doubled up' or overcrowded housing scenarios, or in single-room occupancy (SRO) dwellings Food insecurity has been associated with homelessness in general samples of low-income households (12) as well as in studies of specific demographic groups, including families headed by single mothers (13) and street youth (14,15) . Other studies have found high rates of food insecurity among homeless or unstably housed individuals with co-occurring health or mental health conditions such as HIV/ AIDS, diabetes and psychiatric impairments (9,(16)(17)(18)(19)(20) . These studies have generally found that food insecurity is associated with worse health outcomes and greater drug and sex-related risk behaviours for people with these conditions.…”
mentioning
confidence: 99%
“…This theoretical framework specifies that in addition to proximal biomedical influences, a range of sociopolitical, economic and geographic factors serve as 'upstream' determinants of health and disease (29) . Within a social determinants of health framework, the literature on food insecurity has positioned this issue as both an intermediary condition that influences a number of other health conditions and health behaviours, and a discrete health outcome that is shaped by social, economic and healthrelated factors (5,7,18,19,(30)(31)(32)(33) . Drawing from this literature, we selected social-financial, health-risk and demographic covariates for our analysis.…”
mentioning
confidence: 99%
“…This is largely a policy failure. For example, Wang et al (2013) found that food insecurity was associated with HIV risk behaviors among individuals re-entering the community from prison. Specifically, individuals who did not eat for an entire day were more likely to report risky sex (exchanging sex for money and sex while intoxicated or high) than were those who had at least a meal a day.…”
Section: Discussionmentioning
confidence: 99%